Step 1: Combine like terms
To combine the x-terms, we subtract 5x from both sides and add 10x to both sides of the equation:
-6x + 10x - 5x - 12 = -10x + 10x + 7 - 1
Simplified equation after combining like terms: -x - 12 = 7 - 1
Step 2: Get x-terms on the same side of the equation
To accomplish this, we can add x to both sides of the equation:
-x - 12 + x = 7 - 1 + x
Simplified equation after moving x-terms to one side: -12 = 7 - 1 + x
Step 3: Get constants on the same side of the equation
Subtracting 7 and 1 from both sides of the equation:
-12 - 7 - 1 = 7 - 1 - 7 - 1 + x
Simplified equation after moving constants to one side: -12 - 8 = x
Step 4: Get the x by itself by using the inverse operation
To isolate x, we simplify the equation further:
-20 = x
The solution to the equation is x = -20.
Fill in the blanks to follow the steps in solving the equation:
5x−12−6x=−10x+7−1
Step 1: Combine like terms Response area
Step 2: Get x-terms on same side of equation
Step 3: Get constants on same side of equation
Step 4: Get the x by itself by using the inverse operation
3 answers
Bruh that answer is wrong
Fill in the blanks to follow the steps in solving the equation:
5x−12−6x=−10x+7−1
Step 1: Combine like terms Response area
Step 2: Get x-terms on same side of equation
Step 3: Get constants on same side of equation
Step 4: Get the x by itself by using the inverse operation
Fill in the blanks to follow the steps in solving the equation:
5x−12−6x=−10x+7−1
Step 1: Combine like terms Response area
Step 2: Get x-terms on same side of equation
Step 3: Get constants on same side of equation
Step 4: Get the x by itself by using the inverse operation
Step 1: Combine like terms
To combine the x-terms, we subtract 6x from both sides and add 10x to both sides of the equation:
5x - 6x - 12 = -10x + 10x + 7 - 1
Simplified equation after combining like terms: -x - 12 = 7 - 1
Step 2: Get x-terms on the same side of the equation
To accomplish this, we can add x to both sides of the equation:
-x - 12 + x = 7 - 1 + x
Simplified equation after moving x-terms to one side: -12 = 7 - 1 + x
Step 3: Get constants on the same side of the equation
Subtracting 7 and 1 from both sides of the equation:
-12 - 7 - 1 = 7 - 1 - 7 - 1 + x
Simplified equation after moving constants to one side: -20 = x
Step 4: Get the x by itself by using the inverse operation
To isolate x, we simplify the equation further:
x = -20
The solution to the equation is x = -20.
To combine the x-terms, we subtract 6x from both sides and add 10x to both sides of the equation:
5x - 6x - 12 = -10x + 10x + 7 - 1
Simplified equation after combining like terms: -x - 12 = 7 - 1
Step 2: Get x-terms on the same side of the equation
To accomplish this, we can add x to both sides of the equation:
-x - 12 + x = 7 - 1 + x
Simplified equation after moving x-terms to one side: -12 = 7 - 1 + x
Step 3: Get constants on the same side of the equation
Subtracting 7 and 1 from both sides of the equation:
-12 - 7 - 1 = 7 - 1 - 7 - 1 + x
Simplified equation after moving constants to one side: -20 = x
Step 4: Get the x by itself by using the inverse operation
To isolate x, we simplify the equation further:
x = -20
The solution to the equation is x = -20.